La cocina de los venenos : aspectos de la criminalidad en el Nuevo Reino de Granada, siglos XVII y XVIII - Ariza Martínez, Juan Sebastián (Opera prima (Editorial Universidad del Rosario), 2015)
During the 17th and 18th centuries there were several cases presented to the Court of Justice of the Nuevo Reino de Granada, which alleged that several people were exercising the healing arts without the appropriate medical titles. By then, it was believed that those who used herbs and spells as therapeutic methods, usually women, should be judged as yerbatera-poisoners, because rather to cure the patients, they killed those who consume their preparations. The document states that the criminal processes of poisoning are a prism in which different problems of the neogranadina colonial period converge; such as health, medical trades, illness, magical-religious beliefs, womans ideal, delinquency and the dynamics of Spanish institutions, among others. In this way, is study how was the relationship between the legal, criminal law (issued by the Crown) and behavior "diverted" (relating to the crime of poisoning) of the habitants of the Nuevo Reino de Granada, between the 17th and 18thcenturies. For this, are going to be indexed from different perspectives, some issues of the colonial world neogranadino related to the rumors, the gossip, and the importance of spoken communication in the viceroyalty; the problem of honor, as one of the most outstanding virtues of the time and beliefs of popular culture in relation to poisoning and different healing methods.